THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND AWARENESS ON CAFE YUMA BANDUNG PURCHASE DECISIONS - Frans Sudirjo; I Nyoman Tri Sutaguna; Endang Silaningsih; Farida Akbarina; Muhammad Yusuf (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study employs quantitative and descriptive methods." Customers of Cafe Yuma Bandung make up the majority of the research sample. This survey comprises a sample of Cafe Yuma Bandung customers who are at least 18 years old, have social media profiles, and are familiar with the cafe. Yuma Bandung on social media Purposive sampling was utilised to acquire data, and 89 participants took the survey. This number exceeds the required value of 0.70, indicating that the research findings are trustworthy. The overall reliability test resulted in a score of 0.902 for each of the social media marketing variables (X1), 0.874 for brand awareness (X2), and 0.902 for purchasing decisions (X3). This study included a quantitative descriptive research design, descriptive statistics, and PLS analysis. According to the findings of the study, social media marketing has a favourable and significant impact on purchasing decisions. Keyword: Social Media Marketing, Brand Awareness, Keputusan Pembelian This study employs quantitative and descriptive methods." Customers of Cafe Yuma Bandung make up the majority of the research sample. This survey comprises a sample of Cafe Yuma Bandung customers who are at least 18 years old, have social media profiles, and are familiar with the cafe. Yuma Bandung on social media Purposive sampling was utilised to acquire data, and 89 participants took the survey. This number exceeds the required value of 0.70, indicating that the research findings are trustworthy. The overall reliability test resulted in a score of 0.902 for each of the social media marketing variables (X1), 0.874 for brand awareness (X2), and 0.902 for purchasing decisions (X3). This study included a quantitative descriptive research design, descriptive statistics, and PLS analysis. According to the findings of the study, social media marketing has a favourable and significant impact on purchasing decisions.